INNOVATIVE FINANCIAL INSTRUMENTS FOR THE FORMATION OF INVESTMENT RESOURCES IN THE AGRICULTURAL SECTOR OF UKRAINE - Михайлова, Любовь; Михайлов, Андрей (Modern engineering and innovative technologies, 2017)
It proves the need to use innovative financial instruments for the formation of investment resources in the agricultural sector of the economy through a combination of internal (agricultural receipts, leasing services, forwards, bank financing) and extern